2007
DOI: 10.1103/physrevb.75.205408
|View full text |Cite
|
Sign up to set email alerts
|

Structural, optical, and electrical properties ofMgyTi1yHxthin films

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.Downloaded from the University of Groningen/UMCG research database (Pure): http://www.rug.nl/research/portal. For technical reasons the number of authors shown on this cover page is limited to 10 maximum. The structural, optical, and electrical transformations induced by hydrogen absorption and/or desorption in Mg-Ti thin films p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
130
0
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 120 publications
(149 citation statements)
references
References 38 publications
13
130
0
4
Order By: Relevance
“…В двухкомпонентных плёнках на основе магния Mg y Ti 1y и Mg y Ni 1y процессы поглощения водорода также взаимосвязаны с изменениями их оптических свойств и электропроводимости [41][42][43]. Это во многом связано с тем, что фаза MgH 2 является ди-электриком и имеет менее компактную решётку, чем магний.…”
Section: оптические и электрофизические характеристики плёнок на осноunclassified
See 1 more Smart Citation
“…В двухкомпонентных плёнках на основе магния Mg y Ti 1y и Mg y Ni 1y процессы поглощения водорода также взаимосвязаны с изменениями их оптических свойств и электропроводимости [41][42][43]. Это во многом связано с тем, что фаза MgH 2 является ди-электриком и имеет менее компактную решётку, чем магний.…”
Section: оптические и электрофизические характеристики плёнок на осноunclassified
“…Коэффициент пропускания световых волн у такого материала с ростом содержания в нём водорода увели-чивается, а коэффициент отражения уменьшается (рис. 5, а) [41]. Происходящие при этом структурные изменения коррелируют с ростом электросопротивления (рис.…”
Section: оптические и электрофизические характеристики плёнок на осноunclassified
“…The equality of the molar volumes of TiH 2 and Mg has been used to explain the structural stability of these metastable thin film alloys. 15,16 Notten and co-workers [20][21][22] and Borsa et al 6,15 showed that for a high titanium content, x Շ 0.8, the structure of the hydrides is fluoritelike. Hydrides with a lower titanium content adopt a rutilelike structure, similar to that of ␣-MgH 2 .…”
Section: Introductionmentioning
confidence: 99%
“…In experiments, usually somewhat less than two hydrogen atoms per metal atom are absorbed. 15 Electrochemically 1.7 hydrogen atoms per metal atom can be absorbed and desorbed reversibly. 25 The high-pressure crystalline phase Mg 7 TiH 16 contains two hydrogen atoms per metal atom.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation